Anonimitas Netizen di Media Sosial - Dian Harmaningsih; Susi Yunarti; Wijayanti Wijayanti (Universitas Persada Indonesia YAI, 2021)
This study aims to explain about the phenomenon of deindividuation appears in cyberspace,especially in social media. The research question is why are netizens on social media makingscathing comments about the COVID-19 vaccine? This study uses De-individuation theory -Gustav Le Bon and descriptive qualitative research methods by analyzing various commentsfrom netizens on Facebook and You tube accounts. Data collection was carried out in the periodNovember to December 2020. The results of the study revealed that the phenomenon ofdeindividuation occurs on social media, especially by netizens who use accounts that are notreal names and anonym. Meanwhile, netizens who use self-explanatory names tend to makemore polite comments. This phenomenon shows that the courage to use harsh words ignoresnorms and ethics that makes them think that their identity is unknown to public. Even the mediahas suggested to comment clearly, but no sanctions are applied, so netizens have the freedomto make harsh comments like He is the most correct. This condition of anonymity is the basisfor a person's lack of self-awareness